Comparative analysis of drugs frequently suspected of causing adverse drug reactions reported via the spontaneous reporting system versus in a prospective multicentre cohort study in hospital emergency departments - Graeff, Verena Ursula; Wehler, Markus; Dormann, Harald; Stingl, Julia; Just, Katja S.; Eisert, Albrecht (Journal of Clinical Medicine, 2025)
Background/Objectives: Pharmacovigilance aims to identify, assess, and minimize drug risks, with spontaneous reporting playing a central role. However...